ENDOPOLYPLOIDY OF ENDANGERED PLANT SPECIES LIGULARIA SIBIRICA IN DIFFERENT ENVIRONMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The goal of this study was to detect endopolyploidy of Ligularia sibirica from populations existed in different ecological conditions. This is important step to elaborate the appropriate protection measures of rare and endangered species, which should be based on understanding of ongoing processes in populations. From this point of view the knowledge of genetic diversity, including endopolyploidy level between and within populations, is crucial. L. sibirica is endangered and protected plant species in Latvia which is included in the protected plants list of EU Habitat directive 92/43/EEK Annexes 2 and 4. Perennial herbaceous plant L. sibirica is one of two species of genus Ligularia in Europe. According to the previous data, this species has been disappeared from all previously known locations in Latvia. However, some new locations were found in central part of the country recently. Determination of edopolyploidy level of L. sibirica was performed by the BD FACSJazz® cell sorter (BD Biosciences, USA) with flow cytometer function. In young leafs nine relative fluorescence DNA peaks from 2C up to 64 C were detected. The most common was 2C peak presented in 93% and 63% of samples from Zušu-Staiņu sulphur spring and Krustkalni Nature reserve populations respectively.